Study the Behavior of Steel Connections Used in Metal Structures with the Help of the Finite Element Method and the Use of the CATIA V5 Program - هترة علي (Latakia University Journal -Engineering Sciences Series, 2021)
This research presents the study of the conductivity of joints used in metal constructions with the help of the finite element method and the use of the CATIA V5 program. The studied model is a steel joints with a plate at its ends connected by screws. We will study the effect of changing the radius the screw of jonction, the thickness of the end plates, and the length of the supporting column. Failure patterns and the results of change in stiffness and rotation were shown, and Von Mises stresses were analyzed on the permissible plates and screws.